A Study of Classroom Behaviour of Prospective Teachers in Relation to Their Teaching Aptitude - Lata, Kusum (INDIAN EDUCATIONAL REVIEW, 2015)
The present study examined the effect of teaching skills on classroom behaviour of prospective teachers in relation to their teaching aptitude. Two hundred prospective teachers were taken from two B.Ed colleges from Mohali district which were equally divided into experimental and control groups. Teacher Aptitude test was administered on both the groups to find out the relationship between classroom behaviour and teaching aptitude. The experimental group was exposed to treatment of teaching skills whereas control group received only theoretical explanation of micro teaching. Classroom behaviour of all the prospective teachers was observed before and after the treatment through- Flanders Interaction Analysis technique. Correlation and ANOVA were used to analyse the data. Results showed that there was no significant correlation between classroom behaviour and teaching aptitude of experimental and control groups prior to intervention. The study further revealed that all the groups (high and low teaching aptitude of experimental and control groups) showed significant differencesin their mean scores after the treatment.